The Therapeutic Effect of PLAG against Oral Mucositis in Hamster and Mouse Model - Lee, Ha-Reum; Yoo, Nina; Kim, Joo Heon; Sohn, Ki-Young; Kim, Heung-Jae; Kim, Myung-Hwan; Han, Mi Young; Yoon, Sun Young; Kim, Jae Wha (Frontiers in Oncology, 2016)
Chemotherapy-induced mucositis can limit the effectiveness of cancer therapy and increase the risk of infections. However, no specific therapy for protection against mucositis is currently available. In this study, we investigated the therapeutic effect of PLAG (1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol, acetylated diglyceride) in 5-fluorouracil (5-FU)-induced oral mucositis animal models. Hamsters were administered 5-FU (80 mg/kg) intraperitoneally on days 0, 6, and 9. The animals’ cheek pouches were then scratched equally with the tip of an 18-gauge needle on days 1, 2, and 7. PLAG was administered daily at 250 mg/kg/day. PLAG administration significantly reduced 5-FU/scratching–induced mucositis. Dramatic reversal of weight loss in PLAG-treated hamsters with mucositis was observed. Histochemical staining data also revealed newly differentiated epidermis and blood vessels in the cheek pouches of PLAG-treated hamsters, indicative of recovery. Whole blood analyses indicated that PLAG prevents 5-FU–induced excessive neutrophil transmigration to the infection site and eventually stabilizes the number of circulating neutrophils. In a mouse mucositis model, mice with 5-FU–induced disease treated with PLAG exhibited resistance to body-weight loss compared with mice that received 5-FU or 5-FU/scratching alone. PLAG also dramatically reversed mucositis-associated weight loss and inhibited mucositis-induced inflammatory responses in the tongue and serum. These data suggest that PLAG enhances recovery from 5-FU–induced oral mucositis and may therefore be a useful therapeutic agent for treating side effects of chemotherapy, such as mucositis and cachexia.